The Effect of Board Independence on the Earnings Quality: Evidence from Portuguese Listed Companies - Sandra Alves (Australasian Accounting, Business and Finance Journal, 2014)
Agency theory suggests that independent outside board members may have an important monitoring function of the financial reporting process. As a result, boards with more independent directors have a tendency for increased monitoring and are therefore expected to insist on better earnings quality. This study examines whether board independence improves earnings quality by reducing earnings management in Portugal, a country with significantly different institutional and legal characteristics from the Anglo-Saxon countries. Using ordinary least square (OLS) and two stage least squares (2SLS) techniques to control potential simultaneity problems between board independence and earnings quality, we find evidence that independent board members improve earnings quality by reducing earnings management for a sample of Portuguese listed firms. This result suggests that strengthening the independence of boards by appointing more independent board members is a positive step toward improving earnings quality.
Keywords: board independence; earnings quality; discretionary accruals